Elk-1 a Transcription Factor with Multiple Facets in the Brain - Besnard, antoine; Galan, Beatriz; Vanhoutte, peter; Caboche, Jocelyne (Frontiers in Neuroscience, 2011)
The ternary complex factor (TCF) Elk-1 is a transcription factor that regulates immediate early gene (IEG) expression via the Serum Response Element (SRE) DNA consensus site. Elk-1 is associated with a dimer of Serum Response Factor (SRF) at the SRE site, and its phosphorylation occurs at specific residues in response to Mitogen Activated protein Kinases, including c-Jun-Nterminal Kinase (JNK), p38/MAPK and ERK (Extracellular-signal Regulated Kinases). This phosphorylation event is critical for triggering SRE-dependent transcription. Although MAPKs are fundamental actors for the instatement and maintenance of memory, and much investigation of their downstream signaling partners have been done, no data yet clearly implicate Elk-1 in these processes. This is partly due to the complexity of Elk-1 sub-cellular localization, and hence functions, within neurons. Elk-1 is present in its resting state in the cytoplasm, where it colocalizes with mitochondrial proteins or microtubules. In this particular sub-cellular compartment, overexpression of Elk-1 is toxic for neuronal cells. When phosphorylated by the MAPK/ERK, Elk-1 translocates to the nucleus where it is implicated in regulating chromatin remodeling, SRE-dependent transcription, and neuronal differentiation. Another post-translational modification is sumoylation, which relocalizes Elk-1 in the cytoplasm. Thus, Elk-1 plays a dual role in neuronal functions: pro-apoptotic within the cytoplasm, and pro-differentiation within the nucleus. To address the role of Elk-1 in the brain, one must be aware of its multiple facets, and design molecular tools that will shut down Elk-1 expression, trafficking or activation, in specific neuronal compartments. We summarize in this review the known molecular functions of Elk-1, its regulation in neuronal cells, and present evidence of its possible implication in model systems of synaptic plasticity, experience-learning, but also in psychiatric or neurodegenerative diseases.